Native T1 mapping of autoimmune pancreatitis as a quantitative outcome surrogate - Zhu, Liang; Lai, Yamin; Makowski, Marcus; Zhang, Wen; Sun, Zhaoyong; Qian, Tianyi; Nickel, Dominik; Hamm, Bernd; Asbach, Patrick; Duebgen, Matthius; Xue, Huadan; Jin, Zhengyu (European radiology, 2019)
Objectives To investigate the ability of T1 mapping to visualize and quantify the short-term and mid-term response of autoimmune pancreatitis (AIP) to corticosteroid treatment (CST) and to correlate T1 relaxation time of the pancreas with clinical status and serum IgG4 level. Methods The institutional review board approved this prospective study, and all patients provided written informed consent. Pancreatic MRI including native T1 mapping was performed in 39 AIP patients before and during CST, and 40 patients without pancreatic diseases served as control. T1 relaxation time of the pancreatic head, body, and tail was measured in each patient. Clinical symptoms and serum IgG4 level of the patients were recorded. Results The native T1 relaxation time of AIP was significantly elongated compared to normal pancreatic tissue (1124.5 ms ± 95.7 ms vs 784.3 ms ± 41.8 ms, p < 0.001). After short-term CST (4 weeks), T1 relaxation time of AIP already shortened significantly (957.2 ms ± 97.3 ms, p < 0.001). After mid-term CST (12 weeks), the T1 relaxation time further shortened towards normalization (844.2 ms ± 71.6 ms, p < 0.001). In 33 AIP patients with elevated serum IgG4 at baseline, T1 relaxation time demonstrated a significant positive correlation with serum IgG4 level ( r = 0.329, p = 0.011). In six AIP patients with normal serum IgG4 level at baseline, T1 relaxation time shortening preceded or was in accordance with symptom relief. Conclusions Native T1 mapping can be used to assess parenchymal inflammation of AIP and to quantify response to treatment. It provides a quantitative outcome surrogate for AIP. Key Points • Parenchymal inflammation in autoimmune pancreatitis results in T1 relaxation time elongation, which shortens after effective treatment. • T1 relaxation time of the pancreas correlates with serum IgG4 level, and in serum IgG4-negative AIP patients, T1 relaxation time shortening predicts clinical improvement. • T1 mapping provides a quantitative outcome surrogate for AIP.